Adventure time. The complete sixth season [videorecording (DVD)] (Warner Bros. Ent., 2016)
It's one crazy adventure after another for human boy, Finn, and his best friend, Jake, a 28-year old dog with magical powers. They're out to have the most fun possible and they sure do find it exploring the Land of Ooo. Whether it's saving Princess Bubblegum, battling zombie candy, taunting the Ice King or rocking out with Marceline the Vampire Queen, with Finn and Jake it's always Adventure Time.